Evaluation of analgesic and anti-inflammatory activities of Terminalia arjuna leaf - Tarun K Karan3, Sanjib Bhattacharya4, Ashoke K Ghosh5 , Pallab K Haldar3*, Moulisha Biswas1, Kaushik Biswas2 (Journal of Phytology, 2011)
Terminalia arjuna Roxb. (Combretaceae), commonly known as Arjuna is traditionally used for several medicinal purposes in India. The present study assessed analgesic and anti-inflammatory activities of its leaf. Dried and crushed leaves of Terminalia arjuna were defatted with petroleum ether and then extracted with methanol. The methanol extract (META) at the doses of 100 mg/kg and 200 mg/kg body weight was subjected for evaluation of analgesic and anti-inflammatory activities in experimental animal models. Analgesic activity was evaluated by acetic acid-induced writhing, hot plate and formalin tests in Swiss albino mice; and acute anti-inflammatory activity was evaluated by carrageenan, histamine and dextran-induced paw oedema in Wister albino rats. Aspirin and indomethacin were employed as reference drugs for analgesic and anti-inflammatory studies respectively. In the present study, the methanol extract of the leaves of Terminalia arjuna demonstrated significant analgesic and acute anti-inflammatory activities in the tested models. Key words: Terminalia arjuna Roxb., Analgesic, Anti-inflammatory, Pain <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Moulisha Biswas et al. Evaluation of analgesic and anti-inflammatory activities of Terminalia arjuna leaf. J Phytol 3/1 (2011) 33-38.